Nomogram to Predict Tumor-Infiltrating Lymphocytes in Breast Cancer Patients - Feng, Jikun; Li, Jianxia; Huang, Xinjian; Yi, Jiarong; Wu, Haoming; Zou, Xuxiazi; Zhong, Wenjing; Wang, Xi (Frontiers in Molecular Biosciences, 2021)
Abstract: Background: Tumor-infiltrating lymphocytes (TILs) play important roles in the prediction of prognosis and neoadjuvant therapy (NAT) efficacy in breast cancer (BRCA) patients, in this study, we identified clinicopathological factors related to BRCA TILs, then to construct and validate nomogram to predict high density of TILs. Methods: A total of 826 patients diagnosed with BRCA in Sun Yat-Sen University cancer center were enrolled in nomogram cohort. TILs were assessed using H&E staining by two pathologists. Complete clinical data were collected for analysis. Then the enrolled patients were split into a training set and validation set at a ratio of 8:2. and the backward multivariate binary logistic regression model was used to establish nomogram for predicting BRCA TILs, which were further evaluated and validated using the C-index, receiver operating characteristic (ROC) curves and calibration curves. Then another independent NAT cohort of 115 patients was established for verifying this nomogram in NAT efficacy prediction. Results: TILs were significantly correlated with body mass index (BMI), tumor differentiation, ER, PR, HER2 expression , Ki67, blood biochemical indicators including total bilirubin (TBIL), indirect bilirubin(IBIL), total protein(TP), Globulin(GLOB), inorganic phosphorus(IP), calcium (Ca). In which ER expression level[OR=0.987,95%CI(0.982-0.992),P<0.001],IP[OR=4.462,95%CI(1.171~17.289),P=0.029],IBIL [OR=0.906, 95%CI (0.845-0.966), P=0.004] and TP[OR=1.053,95%CI(1.010-1.098,P=0.016)] were independent predictors of TILs. Then nomogram was established, for which calibration curves (C-index = 0.759) and ROC curve (AUC=0.759, 95%CI 0.717-0.801) in training sets, calibration curves (C-index = 0.708) and ROC curve (AUC=0.708, 95%CI 0.617-0.800) in validation sets demonstrated great evaluation efficiency. Besides ，independent NAT cohort verified this nomogram can distinguish patients with greater NAT efficacy(p=0.041). Conclusion: The finds of clinico-pathological factors associated with TILs could help clinicians to understand the tumor immunity of BRCA and improve treatment system for patients, and the established nomogram with high evaluation efficiency may be used as a complement tool for distinguishing patients with better NAT efficacy .